Personal Evaluation in Job Search Considering: Vocation, Responsibility and Self-Confidence by Means Of Six Sigma and A Geometric Multivariate Capability Indicator - Tomás José Fontalvo Herrera , Fabio Mejía Zambrano , Ana Gabriela Banquez Maturana (Migration Letters, 2024)
The objective of this research is to evaluate in a technical way the job search performance during the Covid-19 pandemic in Cartagena (Colombia), considering vocation, responsibility and confidence of unemployed people, using Six Sigma and a geometric multivariate capability indicator. As a theoretical foundation, the concepts of Six Sigma metrics, geometric multivariate capability indicator, job search during the COVID-19 pandemic and professional vocation were integrated. As methodology, the study was approached from a positivist-qualitative conception that implied: i) identification of the quality dimensions of the process; ii) approach of the data collection instrument; iii) implementation of the Six Sigma metrics; iv) valuation of the geometric multivariate capability indicator; and, v) rational analysis of the results. As a finding, the performance of the job search is good, having a geometric multivariate capability indicator at 0.67, which is within the range of .